A jurisprudential overlap between fatwa, ijtihad, ijma, qiyas, istislah and istihsan: an appraisal - Chiroma, Magaji; Arifin, Mahamad; Ansari, Abdul Haseeb; Abdullah, Mohamad Asmadi (Serials Publications, 2015)
The relationship that exists between fatwa andijtihad, ijma’, Qiyas,istislah and istihsan is significant to the development of Shari‘ah. Although, the terms seem to be different in the actual sense, but sometimes they do overlap each other, as they all focus in achieving same goal. The paper realized that ijtihad, ijma’, Qiyas, istislah and istihsan could better be described as methodology for arriving at an effective fatwa, than to be described as a legal verdict per se. It is based on this, the paper also suggests that muftis, while considering the importance of the above concepts to the role of fatwa in the contemporary society, should expose their talents in explaining the maqasid ash- Shari‘ah (objectives of Shari‘ah) based on the consideration ofmaslahah (public interest) and mafsadah (mischief ) that may likely occur. Fatwa, Ijtihad, Ijma’, Qiyas, Istislah, Istihsan, Jurisprudential Overlap